THE INFLUENCE OF PUBLIC ACCOUNTING FIRM SIZE, AUDIT FEE, AND COMPANY SIZE ON AUDIT QUALITY - Icih; Norhanizah Johari; Anissa Dela Fitri (PT. ZILLZELL MEDIA PRIMA, 2025)
This study seeks to examine the influence of public accounting firm magnitude, audit fees, and company scale on audit quality. Utilizing quantitative methodology, logistic regression analysis was conducted employing spss version 25 software. The study focused on building materials firms listed on the malaysia stock exchange between 2020 and 2022. Data were extracted from the annual reports of these entities, with a purposive sampling approach involving 27 companies. Findings indicate a statistically significant positive relationship between the size of public accounting firms and audit quality (p < 0.001). Conversely, audit fees (p = 0.738) and company size (p = 0.243) exhibit no significant positive association with audit quality. Hence, the research concludes that public accounting firm magnitude positively impacts audit quality, while audit fees and company size lack significant influence.